NLRP6 Plays an Important Role in Early Hepatic Immunopathology Caused by Schistosoma mansoni Infection - Sanches, Rodrigo C. O.; Souza, Cláudia; Marinho, Fabio Vitarelli; Mambelli, Fábio Silva; Morais, Suellen B.; Guimarães, Erika S.; Oliveira, Sergio Costa (Frontiers in Immunology, 2020)
Schistosomiasis is a debilitating parasitic disease that affects more than 200 million people worldwide and causes approximately 280,000 deaths per year. Inside the definitive host, eggs released by S. mansoni lodge in the intestine and especially in the liver where they induce a granulomatous inflammatory process, which can lead to fibrosis. The molecular mechanisms initiating or promoting hepatic granuloma formation remain poorly understood. Inflammasome activation has been described as an important pathway to induce pathology mediated by NLRP3 receptor. Recently, other components of the inflammasome pathway, such as NLRP6, have been related to liver diseases and fibrotic processes. Nevertheless, the contribution of these components in schistosomiasis-associated pathology is still unknown. In the present study, using dendritic cells, we demonstrated that NLRP6 sensor is important for IL-1β production and caspase-1 activation in response to soluble egg antigens (SEA). Furthermore, the lack of NLRP6 has been shown to significantly reduce periovular inflammation and, collagen deposition in hepatic granulomas and mRNA levels of α-SMA and IL-13. Livers of Nlrp6-/- mice showed reduced levels of CXCL1/KC, CCL2 and, CCL3 chemokines, IL-5 and IL-10 as well as and MPO and EPO enzymatic activity. Consistently, the frequency of macrophage and neutrophil populations were lower in the liver of NLRP6 knockout mice, after six weeks of infection. Finally, it was further demonstrated that the onset of hepatic granuloma and collagen deposition were also compromised in Caspase-1-/-, IL-1R-/- and Gsdmd-/- mice. Our findings suggest that the NLRP6 inflammasome is an important component for schistosomiasis-associated pathology.